Effect of carrageenan coating with clove oil on quality of raw beef - Mislang, Maria Romina C.; Cornago, Djanna F. (2009.)
ABSTRACT The effect of a clove oil-carrageenanan coating on the quality of beef slices was determined throughout 7 days of storage. Two percent (w/v) carrageenan, 0.75% glycerol (w/v) consisted the coating solutions, with additional 2.5% (v/v) clove oil and 0.1% Tween 80 (w/v) for the clove oil-incorporated coating. The color, weight loss percentage and microbial quality of clove-oil-treated beef slices were compared with uncoated slices and carrageenan-coated beef slices. Clove oil-treated slices showed better redness and chroma values, indicating a preservative effect on meat color. However, higher weight losses were observed with clove oil-treated slices than the uncoated samples brought about by increased water loss in the coating where the oil was incorporated. Carrageenan coating tended to sacrifice its moisture first to delay product desiccation. Microbial load was comparable among the treatments, possibly due to partial loss of active oil components during film preparation, decreased antibacterial activity of the clove oil within the film and the presence of phenolic-inhibiting Tween 80 in the film solution. With increased clove oil concentration (5.0%), beef slices exhibited better color with decreasing lightness values and higher redness and chroma values. Microbial growth was also more inhibited at the higher concentration. Higher weight losses were observed with 5.0% clove oil due to increased water vapor sorption because of the increase in hydrophobic components in the carrageenan coating. The study shows that application of a clove oil-carrageenan coating to beef slices is useful in preserving beef quality.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beef; Meat -- Preservation; Clove (Spice.